A case of non-immune hydrops fetalis with maternal mirror syndrome diagnosed by trio-based exome sequencing: An autopsy case report and literature review - Sho Tano; Tomomi Kotani; Masato Yoshihara; Noriyuki Nakamura; Seiko Matsuo; Takafumi Ushida; Kenji Imai; Miharu Ito; Yasuyoshi Oka; Emi Sato; Shin Hayashi; Tomoo Ogi; et al. (Molecular Genetics and Metabolism Reports, 2022)
Non-immune hydrops fetalis (NIHF) indicates the risk for stillbirth. Although the causes vary and most NIHFs have no identifiable cause, recent advances in exome sequencing have increased diagnostic rates.We report a case of NIHF that developed into a giant cystic hygroma complicated by maternal mirror syndrome. Trio-based exome sequencing showed a de novo heterozygous missense variant in the RIT1 (NM_006912: c.246 T > G [p.F82L]). The RIT1 variants are known causative variants of Noonan syndrome (NS; OMIM #163950). The location of the RIT1 variants in the previously reported NS cases with NIHF or/and maternal mirror syndrome was mainly in the switch II region, including the present case.While a further accumulation of cases is needed, exome sequencing, which can identify the variant type in detail, might help predict the phenotype and severity of NIHF.